Improvement of silver nanoparticle impregnation on cotton fabrics using a binder (2017)
In this work, silver nanoparticles were synthesized by the polyol process, which reduces silver nitrate with ethylene glycol. The temperature effect and the polyvinylpyrrolidone (PVP) amount were studied. The temperatures used were 100, 120 and 140 °C. Three ratios of 0.00, 0.25, and 0.50 (% w/w) of PVP/AgNO3 were established. Nanoparticles with sizes less than 30 nm were obtained in conditions of 120 °C and 0.5 % w/w of PVP/AgNO3. Posteriorly, nanoparticles in concentrations of 10 and 20 ppm were deposited on cotton fabric by the pad-dry-cure technique, in order to analyze their bactericidal properties against the Gram positive bacteria Staphylococcus aureus 25923. The tests showed that cotton fabric with nanoparticles in concentrations of 10 and 20 ppm had good bactericidal properties, reducing bacterial colonies by over 98 %. Finally, a washing stability study of the fabrics impregnated with silver nanoparticles was performed, and an acrylic binder was added during the impregnation process. The results were obtained by bacteriological analyzes.